Impact of Family and Friends on Antisocial Adolescent Behavior: The Mediating Role of Impulsivity and Empathy - Álvarez-García, David; González-Castro, Paloma; Núñez, José Carlos; Rodríguez, Celestino; Cerezo, Rebeca (Frontiers in Psychology, 2019)
Adolescence is an especially risky phase for the appearance of antisocial behaviors. Antisocial behavior produces significant individual and social harms, so it is important to provide keys for prevention and treatment. To do that, it is essential to identify the main predictors. The objective of this study is to analyze the effect of family (affection and communication, behavioral control) and friends (antisocial friendships) on adolescent antisocial behavior, as well as the mediating role of adolescent impulsivity and empathy on these relationships. Previously validated questionnaires measuring parental affection and communication, and behavioral control, as well as adolescent impulsivity, empathy, antisocial friendships, and antisocial behavior were applied to 3199 adolescents in Asturias (Spain), aged between 11 and 18 (M = 14.03; SD = 1.39). Descriptive, correlational, and structural equation analysis were performed. Antisocial friendships were a risk factor for antisocial behavior in adolescence, with a moderate effect size. The effect is mostly direct, although it is also indirect through the positive relationship with adolescent impulsivity and low empathy. The two analyzed parenting style dimensions (affection and communication, and behavioral control) demonstrate a protective effect, albeit small, on adolescent antisocial behavior. There is a direct protective effect, but it is mostly indirect through the negative relationship with antisocial friendships and low adolescent empathy. Parental behavioral control can be a risk factor for antisocial behavior, through the positive relationship with adolescent impulsivity. This study helps to clarify the causal mechanisms of antisocial behavior in adolescence, as a basis for its prevention and treatment.